Study of Groundwater Types Using the Vertical Electrical Sounding (VES) Method in the ‘Martani Field’ Ngemplak District of Yogyakarta - Nurul Dzakiya; Muhammad Faizal Zakaria; Dewa Gede Eka Setiawan; Robertus Belardo Laksmana (Journal of Applied Geospatial Information, 2021)
Study of groundwater types using the Vertical Electrical Sounding (VES) method in 'Martani Field’ Ngemplak District of Yogyakarta was done by carrying out eight measurement points to look for groundwater potential. This area is an area on the southern slopes of Mount Merapi which is included in the Yogyakarta Groundwater Basin. The type of lithology is identified based on the measurement of its resistivity value so that there are several types of lithology, namely Breccia (110-670 Ωm), Clay (1.99-10.12 Ωm), Sandstones (17.06-56.82 Ωm) and andesite lava (688-1657 Ωm). The bottom of the aquifer in this basin is composed of rock formations that are impermeable or semi impermeable which are non-aquifer, namely by Breccias, Clay and Andesite Lava. The existence of sandstones that act as aquifers is found near the surface at a depth of <25 m and at a depth of about 60-100 m below the surface so that it is divided into two categories, namely shallow groundwater and deep groundwater.